Use of statistical modelling to investigate the pathogenesis of claw horn disruption lesions in dairy cattle - Randall, L.V.; Green, M.J.; Huxley, J.N. (Elsevier, 2018)
Claw horn disruption lesions (CHDLs) in dairy cattle account for a large proportion of lameness. The aim of this review is to provide an update on the evidence surrounding the pathogenesis of CHDLs, in the context of how statistical modelling has contributed to the validity of available evidence and current thinking. Historically, ‘subclinical laminitis’ has often been used to describe the commonly accepted underlying pathology associated with these lesions, however progress in understanding the aetiopathogenesis of CHDLs and a lack of clear evidence to support the traditional laminitis hypothesis, means use of this terminology has been challenged. With advancements in statistical modelling capabilities within the veterinary field, the multifactorial and complex nature of CHDLs can be more fully explored. This has led to an increased understanding of environmental and animal-based risk factors and their role in the pathogenesis of CHDLs, as well as highlighting future research areas. There is still a need for further research using intervention studies to demonstrate causality for identified risk factors to date, as well as quantifying the impact of these risk factors at the population level. Some important considerations when using and interpreting statistical models in lameness research are discussed with a critical assessment of the key statistical issues in published research investigating the pathogenesis of CHDLs.